Comparison Between Numerical and Experimental Methodologies for Total Enthalpy Determination in Scirocco PWT - Antonio Smoraldi; Luigi Cutrone (Aerospace)
Arc-jet facility tests are critical for replicating the extreme thermal conditions encountered during high-speed planetary entry, where the precise determination of flow enthalpy is essential. Despite its importance, a systematic comparison of methods for determining enthalpy in the Scirocco Plasma Wind Tunnel had not yet been conducted. This study evaluates three experimental techniques—the sonic throat method, the heat balance method, and the heat transfer method—under various operating conditions in the Scirocco facility, employing a nozzle C configuration (10° half-angle conical nozzle with a 90 cm exit diameter). These methods are compared with computational fluid dynamics (CFDs) simulations to address discrepancies between experimental and predicted enthalpy and heat flux values. Significant deviations between measured and simulated results prompted a reassessment of the numerical and experimental models. Initially, the Navier–Stokes model, which assumes chemically reacting, non-equilibrium flows and fully catalytic copper walls, underestimated the heat flux. By incorporating partial catalytic behavior for the copper probe surface, the CFD results showed better agreement with the experimental data, providing a more accurate representation of heat flux and flow enthalpy within the test environment.